2015
DOI: 10.1108/bpmj-10-2014-0099
|View full text |Cite
|
Sign up to set email alerts
|

The central role of knowledge management in business operations

Abstract: Purpose – Knowledge Management (KM) is a contemporary research field of high interest for both academics and practitioners. For more than 15 years, successful companies have used KM as their most valuable source of competitive advantage. The purpose of this paper is attempt to extend the existing empirical approaches (research models), by focusing on the process of KM and its diffusion throughout the organisation. Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 101 publications
0
43
2
1
Order By: Relevance
“…While there are substantial researches that reported an association between business success and knowledge sharing (Egbu et al, 2005;Ngah & Jusoff, 2009;Chatzoudes et al, 2015), this study appears to have found insufficient empirical evidence to support this contention. This phenomenon occurs, perhaps due the low level of participation on such practice among employees of small firms (Durst & Runar Edvardsson, 2012).…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations
“…While there are substantial researches that reported an association between business success and knowledge sharing (Egbu et al, 2005;Ngah & Jusoff, 2009;Chatzoudes et al, 2015), this study appears to have found insufficient empirical evidence to support this contention. This phenomenon occurs, perhaps due the low level of participation on such practice among employees of small firms (Durst & Runar Edvardsson, 2012).…”
Section: Discussioncontrasting
confidence: 48%
“…The strategic importance of technological usage is well acknowledged in the literature as a factor that could enhance business success (Jasra et al, 2011;Raymond & Bergeron, 2008;Chatzoudes et al, 2015). Firms that utilise the latest technology tend to capture customers more than their competitors (Valacich & Schneider, 2014).…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Argumentatively, it can also be maintained that knowledge management can act as an antecedent of knowledge‐worker satisfaction. The arguments are as follows (e.g., Chatzoudes et al., ; Chou et al., ; Kianto et al., ; Nonaka & Takeuchi, ; Razmerita, Kirchner, & Nielsen, ; Shannak, ; Singh & Sharma, ; Tseng & Fan, ). First, the literature review posits that knowledge management should be evaluated by the subjective measures like the satisfaction of knowledge workers instead of objective measures.…”
Section: Literature Reviewmentioning
confidence: 99%